ANALYSIS OF THE EFFECT OF TRUST, PRIVACY, AND EFFICIENCY ON E-SATISFACTION IN FORMING E-LOYALTY IN TOKOPEDIA CUSTOMERS IN SURABAYA - Wiwiek, Wiwiek (RIMA - Research In Management and Accounting, 2020)
This study aims to analyze the effect of Trust, Privacy dan Efficiency; and lastly, the effect of Customer Satisfaction on loyalty consumer of Tokopedia in Surabaya. The sample used in this study are Tokopedia consumer, domicile in Surabaya, having the Tokopedia application, knowing Tokopedia's privacy information, making repeated purchases on Tokopedia in the past 1 (one) year This study used 165 respondents and SPSS 22.0 to process the data. This model was developed in order to conduct research on E-Loyalty conducted on the online shopping site Tokopedia in Surabaya. This research model is formed from the relationship between Trust, Privacy, Efficiency and E-Satisfaction. Based on the data processing that has been done, it is found that Trust and Privacy have a positive and significant influence on E-Satisfaction; E-Satisfaction has a positive and significant effect on E-Loyalty